The Maturing of Hormesis as a Credible Dose-Response Model - Edward J. Calabrese (SAGE Publishing, 2003)
Hormesis is a dose-response phenomenon that has received little recognition, credibility and acceptance as evidenced by its absence from major toxicological/risk assessment texts, governmental regulatory dose-response modeling for risk assessment, and non-visibility in major professional toxicological society national meetings. This paper traces the historical evolution of the hormetic dose-response hypothesis, why this model is not only credible but also more common than the widely accepted threshold model in direct comparative evaluation, and how the toxicological community made a critical error in rejecting hormesis, a rejection sustained over 70 years.